PENGARUH METODE BERCERITA BUKU BERGAMBAR TERHADAP KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN DI TK TADIKA PURI PEKANBARU - Novita, Evlin; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : The effect of Picture Book Tells Methods Speech Against Children Aged 5-6 Years On Tk Tadika Castle Pekanbaru. Language plays a very important in a child's life, because through language the child can communicate with the surrounding environment, and expressing ideas or thoughts to others. Initial survey that has been done in kindergarten Tadika Castle Pekanbaru, children are still often mispronouncing words such as the word